The inclusion of extract from aerial part of Scutellaria baicalensis in feeding of pearl gentian grouper (Epinephelus fuscoguttatus♀ × Epinephelus lanceo-latus♂) promotes growth and immunity. Issue 127 (August 2022) - Xia, Yi-Teng; Wu, Qi-Yun; Hok-Chi Cheng, Edwin; Ting-Xia Dong, Tina; Qin, Qi-Wei; Wang, Wen-Xiong; Wah-Keung Tsim, Karl
Abstract: The root of Scutellaria baicalensis (Scutellaria Radix) has been used as herbal medicine for years in China; however, its stem and leaf (aerial part) are considered as waste. The water extract of aerial part of S. baicalensis, named as SBA, having anti-microbial property has been applied in fish aquaculture. To extend the usage of SBA in fish feeding, SBA was employed to feed pearl gentian grouper (a hybrid of Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂), and subsequently the total fish output, the levels of digestive enzymes and inflammatory cytokines were determined. Feeding the fish with different doses of SBA for two months, the body length and weight were significantly increased by 5%–10%. In parallel, the expressions of alkaline phosphatase and growth-related factors in bone, liver and muscle of SBA-fed fish were doubled, which could account the growth promoting effect of SBA. Besides, the activity of digestive enzyme, lipase, and the expressions of anti-inflammatory cytokines were markedly stimulated by 2–3 times under the feeding of 3% SBA-containing diet. The results indicated the growth promoting activity of SBA in culture of pearl gentian grouper, as well as the effect of SBA in strengthening the immunity. These beneficial effects of SBA feeding can increase the total yield of pearl gentian grouper in aquaculture. Thus, the re-cycle of waste products during the farming of S. baicalensis herb in serving as fish feeding should be encouraged. Graphical abstract: Image 1 Highlights: Applied the aerial parts of Scutellaria. baicalensis extract in the feeding of pearl gentian grouper ( E . fuscoguttatus♀ × E . lanceolatus♂ ). This additive enhanced the immunity function and health condition of fish. This additive was found with promotion effect on fish's growth. The non-medical part of herbal medicine can be recycled as fish feeding additive to increasing aquaculture production yield.